Technological platform for catchment water safety planning - Vieira, J.M.P. (2018)
Water safety plans is a concept proposed by the World Health Organisation for risk assessment and risk management in drinking water systems. This concept includes the identification of hazards and control points throughout the water cycle from the catchment to the point of consumption. Deterioration in surface and groundwater quality due to sources of pollution impacting the water intake should be identified and monitored allowing effective management and operation of drinking water systems. Land use information, monitoring databases, and hydrodynamics and water quality river modelling can be used to estimate and forecast the spatial and temporal mass transport and attenuation hazards that impact a given drinking water intake. This work presents a technological platform based on the Delft-FEWS software in which databases and models were implemented for supporting catchment water safety plans in different river basins of the NW region of Portugal